Solubility and swelling of soils from native starch. (26th June 2022) - Schmidt, Carolin; Brunner, Meike; Berger, Christiane; Zahn, Susann; Rohm, Harald
Summary: The cleaning of food processing plants is essential for ensuring compliance with quality and hygiene standards. Properties of food‐borne soils such as solubility and swelling are relevant and provide information concerning their cleanability. In the context of cleaning processes in food industry, the aim of this study was to determine the impact that different cleaning fluids exhibit on the solubility and swelling behaviour of soils consisting of amylose‐ rich native maize, wheat, rice or potato starch or amylopectin rich native waxy maize starch. For this purpose, a process for the preparation of starch pastepowder, mimicking starch soils, was developed. After swelling in water or 20 g kg −1 NaOH at 25 or 55 °C, the solubility and the water binding capacity (WBC) of the starch powders were determined. The solubility of amylose rich starch paste powders was significantly higher in NaOH, whereas amylopectin rich waxy maize starch paste powder dissolved significantly better in water. The use of NaOH resulted in a significant decrease of the WBC of most starches. While a higher solubility and WBC was found for wet maize starch soils (starch paste) than for dried maize starch soils (starch paste powder), solubility and swelling of waxy maize starch soils were not affected by the residual moisture. Abstract :